INNOVATIVE BEHAVIOR OF SMALL AND MEDIUM ENTERPRISES DURING THE ECONOMIC CRISIS - Alexandru, RUSEI (Strategii Manageriale, 2014)
Innovation is an area increasingly attractive to most companies. During and after the crisis, more and more companies are trying to expand their business horizons, to change the organization to discover new products and services in order to maintain operational status, and this can be done only through innovation. The business environment in Romania was heavily influenced by the global crisis in the period 2008-2013: entrepreneurship has become vulnerable due to uncertainty of the economic environment and many SMEs have left the market. In order to survive in these conditions, many companies have had to change the way have worked, and was one of the means innovation. The European Union has undertaken studies that examined this issue for each country, as well as comparisons with other countries. This paper identifies the empirical relationship between innovation (both technological and organizational one) based on published outcomes of European Union-Directorate for Research and Innovation and SMEs in Romania results in this period. Hypothesis that released this paper is that innovation was one of the means by which companies remained in operation during the period 2008-2013. To verify this hypothesis, I will check the results of innovation indicators in Romania in the period 2008-2013 and will check which business organizations remain in operation during this period, based on my correlation between innovation, economic performance and entrepreneurial performance.